THE SOCIAL DIMENSION OF SUSTAINABLE DEVELOPMENT: EMPLOYMENT, UNEMPLOYMENT AND POVERTY AS SUSTAINABILITY MEASUREMENT INDICATORS IN ALGERIA. CASE OF THE CITY OF SKIKDA - Bourahla Nouhed,; Zennir Rabah,; Guessoum Djamel Eddine, (International Journal of Innovative Technologies in Social Science, 2024)
In this article we will discuss a topic of a big importance which is the calculation of the social sustainability of sustainable development in the city of Skikda using fundamental indicators for such kind of study that are: employment, unemployment and poverty, the latter are basic elements for human development because they have a direct link with the assurance of economic growth and the elimination of the poverty, from the point of view that unemployment and the employment aim to fight against poverty, avoid the inequalities and the destruction of social relations as well as the exclusion, in order to ensure social cohesion and the partnership. The analysis of the different data in the city of Skikda confirmed to us that within our study area we can speak of socially equitable or solidarity development, which means we can confirm the social durability of the latter.